Pharmacokinetics, pharmacodynamics, and safety of bococizumab, a monoclonal antibody against proprotein convertase subtilisin/kexin type 9, in healthy subjects when administered in co‐mixture with recombinant human hyaluronidase: A phase 1 randomized trial. Issue 9 (18th July 2018) - Bass, Almasa; Plotka, Anna; Mridha, Khurshid; Sattler, Catherine; Kim, Albert M.; Plowchalk, David R.
Abstract: Aim: Prior to the discontinuation of bococizumab's clinical development, it was considered advantageous to develop an infrequent dosing regimen (eg, monthly). Therefore, we conducted a phase 1 study to evaluate the pharmacokinetics, pharmacodynamics, and safety of bococizumab when administered in co‐mixture with recombinant human hyaluronidase (rHuPH20). Method: Healthy subjects (N = 60) were randomized equally among 4 groups that received a single subcutaneous dose of either bococizumab 150, 300, or 450 mg co‐mixed with rHuPH20 or bococizumab 300 mg alone. Bioavailability and lipid‐lowering effect of bococizumab were evaluated by using ANCOVA models. Results: In the groups administered bococizumab co‐mixed with rHuPH20, dose‐normalized C max and AUCinf were 26.6 to 39.1% and 18.3 to 36.6% greater, respectively, compared with bococizumab 300 mg alone. Despite these increases, mean percent reductions from baseline in low‐density lipoprotein cholesterol were smaller in the bococizumab 300 mg + rHuPH20 group than in the bococizumab 300‐mg group at Day 21 (52.2% and 59.5%, respectively) and were similar at Day 29 (51.7% and 49.6%, respectively). Compared with the group administered bococizumab 300 mg alone, the bococizumab 300 mg + rHuPH20 group did not show a significantly altered AUEC85 (ratio of adjusted means: 102.5%, 90% confidence interval: 96.1‐109.3%) but did show a higher MaxELDL‐C (ratio of adjusted means: 125.4%, 90% confidence interval: 103.3‐152.2%), indicating diminution of efficacy. The most frequent adverse events were injection‐site erythema, injection‐site bruising, and nasopharyngitis; all injection‐site adverse events were mild. Conclusion: Co‐mixture with rHuPH20 increased the bioavailability of bococizumab without proportional increase in pharmacodynamic effect. Trial Registration: ClinicalTrials.gov, NCT02667223. Abstract : Aim Prior to the discontinuation of bococizumab's clinical development, it was considered advantageous to develop an infrequent dosing regimen (eg, monthly). Therefore, we conducted a phase 1 study to evaluate the pharmacokinetics, pharmacodynamics, and safety of bococizumab when administered in co‐mixture with recombinant human hyaluronidase (rHuPH20). Methods Healthy subjects (N = 60) were randomized equally among 4 groups that received a single subcutaneous dose of either bococizumab 150, 300, or 450 mg co‐mixed with rHuPH20 or bococizumab 300 mg alone. Bioavailability and lipid‐lowering effect of bococizumab were evaluated by using ANCOVA models. Results In the groups administered bococizumab co‐mixed with rHuPH20, dose‐normalized C max and AUCinf were 26.6 to 39.1% and 18.3 to 36.6% greater, respectively, compared with bococizumab 300 mg alone. Despite these increases, mean percent reductions from baseline in low‐density lipoprotein cholesterol were smaller in the bococizumab 300 mg + rHuPH20 group than in the bococizumab 300‐mg group at Day 21 (52.2% and 59.5%, respectively) and were similar at Day 29 (51.7% and 49.6%, respectively). Compared with the group administered bococizumab 300 mg alone, the bococizumab 300 mg + rHuPH20 group did not show a significantly altered AUEC85 (ratio of adjusted means: 102.5%, 90% confidence interval: 96.1‐109.3%) but did show a higher MaxELDL‐C (ratio of adjusted means: 125.4%, 90% confidence interval: 103.3‐152.2%), indicating diminution of efficacy. The most frequent adverse events were injection‐site erythema, injection‐site bruising, and nasopharyngitis; all injection‐site adverse events were mild. Conclusion Co‐mixture with rHuPH20 increased the bioavailability of bococizumab without proportional increase in pharmacodynamic effect.